Current challenges in the design of antibody-drug conjugates - Tumey, L. Nathan (Henry Stewart Talks, 2018)
How antibody-drug conjugates work, How payloads are selected, Methods for minimizing toxicity and improving potency, Examples of drugs in clinical trials/market